Osteopetrosis: Gene-based nosology and significance dysosteosclerosis - DEMİRCİOĞLU, SERAP (My University, 2022)
Dysosteosclerosis (DSS) refers to skeletal dysplasias that radiographically feature focal appendicular osteo- sclerosis with variable platyspondyly. Genetic heterogeneity is increasingly reported for the DSS phenotype and now involves mutations of SLC29A3, TNFRSF11A, TCIRG1, LRRK1, and CSF1R. Typical radiological findings are widened radiolucent long bones with thin cortices yet dense irregular metaphyses, flattened vertebral bodies, dense ribs, and multiple fractures. However, the radiographic features of DSS evolve, and the metaphyseal and/ or appendicular osteosclerosis variably fades with increasing patient age, likely due to some residual osteoclast function. Fractures are the principal presentation of DSS, and may even occur in infancy with SLC29A3-asso- ciated DSS. Cranial base sclerosis can lead to cranial nerve palsies such as optic atrophy, and may be the initial presentation, though not observed with SLC29A3-associated DSS. Gene-specific extra-skeletal features can be the main complication in some forms of DSS such as CSF1R- associated DSS. Further genetic heterogeneity is likely, especially for X-linked recessive DSS and cases currently with an unknown genetic defect. Distinguishing DSS can be challenging due to variable clinical and radiological features and an evolving phenotype. However, defining the DSS phenotype is important for predicting complications, prognosis, and instituting appropriate health surveillance and treatment. 1. Introduction Dysosteosclerosis (DSS) is regarded as a skeletal dysplasia (OMIM % 224,300) [1] and was first described in 1934 by Ellis [2] who described 2 brothers from consanguineous English parents and, considered it osteopetrosis (OPT). In 1968, Spranger and colleagues described the disease as a distinct entity [3]. Spranger described the radiological features in a 12-year-old boy as widened radiolucent long bones with thin cortices ends to the dense irregular metaphyses, flattened vertebral bodies, dense ribs, and multiple fractures [3]. DSS is categorized as an osteosclerotic disease, rather than a nonhomogeneous osteosclerosis (i. e. coexistence of radiolucent bones together with dense bones), to differentiate DSS from OPT. Nevertheless, DSS is classified as an OPT- related disorder by the International Skeletal Dysplasia Registry [4] in line with the first report of Ellis [2]. Clinical features of DSS are recur- rent fractures, short stature, failure of tooth eruption, and, sometimes optic atrophy and other cranial nerve palsies, developmental delay, and skin changes [2,3,5–11]. As radiological and clinical findings are vari- able (See below) making a diagnosis can be challenging. Clinical and radiological criteria for DSS are shown in Table 1. Since DSS mimics the clinical and radiological findings of OPT to a degree, candidate gene defects that compromise osteoclast function and/or osteoclastogenesis may be causal. In 2010, Whyte et al. reported an American girl of Turkish heritage with DSS, but with histological features that suggested this was an “osteoclast-poor” form of OPT with a skeletal resorption defect and absence of osteoclasts in bone biopsy [5]. In 2012, delineation of the genetic basis for DSS began with detecting compound heterozygous loss-of-function mutations (c.607 T > C, p. * Marmara University School of Medicine, Department of Paediatric Endocrinology and Diabetes, Fevzi Cakmak Mh. Muhsin Yazicioglu Cd. No 41. 34899, Ust- kaynarca/Pendik, Istanbul, Turkey. E-mail address: serap.turan@marmara.edu.tr. Contents lists available at ScienceDirect Bone journal homepage: www.elsevier.com/locate/bone https://doi.org/10.1016/j.bone.2022.116615 Received 3 July 2022; Received in revised form 9 November 2022; Accepted 12 November 2022
Keywords: Ysosteosclerosis; Bone fractures; Osteopetrosis; Osteosclerosis; Osteopenia; Optic atrophy; Jaw necrosis; Metaphyseal osteosclerosis; Osteosclerotic metaphyseal dysplasia; Pyle disease; Brain abnormalities; Neurodegeneration; Dementia; Leukoencephalopathy; SLC29A3; TNFRSF11A; TCIRG1; LRRK1; CSF1R; TNFSF11